SEASONAL ABUNDANCE OF LIPAPHIS ERYSIMI (KALT.) POPULATION ON MUSTARD - REZA, MD. W.; BISWAS, A.K.; ROY, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
The population built up of mustard aphid, Lipaphis erysimi Kalt, was initiated in the 51 standard week during end of December with initial intensity of 22.67 per plant. The population increased upto 3' standard week in January at the peak of 318.61. Rapid decrease in population was subsequently observed with elimination by the end of February. The aphid population was noticed positively related with temperature but relative humidity had shown slight response on its intensity and without any significant response of little rainfall. At the time of peak infestation the maximum and minimum temperature was 27.37°C and 14.62°C, respectively. The maximum and minimum relative humidity was 95.28 and 62.28%, respectively. In the 4th and 5" standard week the rainfall of 7.40 and 13.10 mm, respectively resulted in lowering down the aphid population from 274.33 to 186.33 per plant. None of the ecological parameters alone was responsible for rapid multiplication of aphid.